Polarization-Dependent Formation of Extremely Compressed Femtosecond Wave Packets and Supercontinuum Generation in Fused Silica - Ilia Geints; Olga Kosareva (Photonics, 2024)
Previous studies of formation of extremely compressed wave packets during femtosecond filamentation in the region of anomalous group velocity dispersion in solid dielectrics mostly considered the case of linearly polarized laser pulses. However, recent results suggest potential applications of polarization state manipulation for ultrafast laser writing of optical structures in bulk solid-state media. In the present work, evolution of radiation polarization parameters during formation of such extreme wave packets at the pump wavelength of 1900 nm in fused silica is studied numerically on the basis of the carrier-resolved unidirectional pulse propagation equation (UPPE). It was revealed that initial close-to-circular polarization leads to higher intensity of the anti-Stokes wing in the spectrum of the generated supercontinuum. Numerical simulations indicate a complex, space–time variant polarization state, and the resulting spatiotemporal electric field distribution exhibits a strong dependence on the initial polarization of the femtosecond pulse. At the same time, electric field polarization tends to linear one in the region with the highest field strength regardless of the initial parameters. The origin of this behavior is attributed to the properties of the supercontinuum components generation during filament-induced plasma formation.